Defenders of faith: Charles V. Suleyman and the magnificent, and the battle for Europe, 1520-1536 - Reston, James, 1941- (New York : Penguin Press, 2009)
History.
Includes bibliographical references and index.
Keywords: Charles V. Holy Roman Empire, 1500-1558.; Holy Roman Empire -- Foreign relations-Turkey.; Turkey-Religion-16th century